KEUNGGULAN SDM DAN BERDAYA SAING TERHADAP KINERJA PT. BANK TABUNGAN NEGARA TBK CABANG DENPASAR PADA MASA PANDEMI COVID-19 - Putu Ari Mulyani; Ni Made Yusmini; Adonia Putriyanti Saradima (Jurnal Ilmiah Satyagraha, 2023)
AbstractBank is an institution that acts as an intermediary that connects parties who have excess funds with those who lack funds in the form of savings and channel them again to the public in the form of credit or other forms, which aims to improve the standard of living of the community considering its very important function for the wheels of the economy and life. Public. the banking industry must have superiority SDM good and have high competitiveness and have good performance. Therefore, a study was carried out with the title Excellence SDM and competitive on performance PT. Bank Tabungan Negara Tbk Cabang Denpasar during the covid-19 pandemic. This study aims to examine the Exceelence of SDM and Competitiveness of Performance PT. Bank Tabungan Negara Tbk Cabang Denpasar. The sample in this study were employess PT. Bank Tabungan Negara Tbk Cabang Denpasar. The research method used in this research is quantitative research using descriptive methods. The process fo collecting research data using a questionnaire distribution technique to 56 respondents and processed using SPSS. The data analysis technique in this study is multiple linear regression using the SPSS (Statistical Package For Social Science) version 23 application. The results obtained by the author are that the advantages of SDM positive and significant effect on performasce, competitineness has a positive and significant effect on performance, SDM excellence and competitiveness together have a positive and positive effect on performance PT. Bank Tabungan Negara Tbk Cabang Denpasar. Keywords: Performance, Superiority sdm, Competitive